Analisa Kasus Indonesia dengan Tiongkok Terkait Zee Perairan Natuna Berdasarkan Unclos Tahun 1982 - Aan Kurniawan (Journal of Judicial Review, 2017)
The purpose of this study is to analyze the juridical case of Indonesia with Tiongkok related Exclusive Economic Zone in Natuna waters which claimed unilaterally by Chinese government, based on United Nation Convention on the Law of the Sea (UNCLOS) Convention 1982. The methodology used in this study is legal juridical normative research. The data used is secondary data obtained from literature study. After all the data collected, then the data then processed and analyzed, the analysis used qualitatively by means of grouping data aspects studied. Hereinafter drawn conclusions related to this research, then described descriptively. Based on this research, the results obtained by the researchers from 2 (two) formulation of the problem, first about the position of Exclusive Economic Zone Natuna Island waters in review of the UNCLOS convention, second about what legal efforts can be made on the claims of the Natuna Exclusive Economic Zone . Based on this research, the writer considers that there are still many weaknesses and weaknesses, especially related to inter-state border guarantees, there should be agreement between neighboring countries on the boundaries of the territory in order to avoid disputes.